2016
DOI: 10.3390/molecules21060743
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Modulatory Effect of Essential Oil from the Leaf of Rhaphiodon echinus (Nees & Mart) Schauer on Some Antimicrobial Drugs

Abstract: Abstract:Background: Rhaphiodon echinus is a weed plant used in the Brazilian folk medicinal for the treatment of infectious diseases. In this study, the essential oil of R. echinus leaf was investigated for its antimicrobial properties. Methods: The chemical constituents of the essential oil were characterized by GC-MS. The antimicrobial properties were determined by studying by the microdilution method the effect of the oil alone, and in combination with antifungal or antibiotic drugs against the fungi Candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
4
20
0
3
Order By: Relevance
“…The activities of the natural products, concerning the antimicrobial agents act by diverse mechanisms of action such as the disintegration of the cytoplasmic membranes, destabilization of the motor proton force (MPF), altering the polarization of the membrane, and the coagulation of the cellular content [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The activities of the natural products, concerning the antimicrobial agents act by diverse mechanisms of action such as the disintegration of the cytoplasmic membranes, destabilization of the motor proton force (MPF), altering the polarization of the membrane, and the coagulation of the cellular content [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported EOs’ synergistic activities when used in combination with antibiotics [ 26 , 27 , 28 ]; nevertheless, to the best of our knowledge, this paper demonstrates for the first time a potent antimicrobial activity of TTO, alone and in combination with different antimicrobials, against clinically relevant MDR Gram-negatives strains (i.e., CR-Kp, CR-Ab, and CR-Pa) and even PDR Kp, towards which the available therapeutic options are very limited or absent. In fact, previous studies investigated the activity of EOs other than TTO against ESBL producing Gram-negatives with unknown sensitivity to carbapenems [ 24 ] or oregano EO against CR-Kp with unknown sensitivity to colistin [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of these natural extracts may include impairment of proteasomal activity, leading to cellular metabolic and structural disruptions that subdue biofilm formation in C. albicans [155]. The role The potency of essential oils derived from plants against Candida has been investigated for over three decades [156], However, it is only recently that some have focused and partially succeeded in identifying new essential oils with a degree of antifungal activity [157,158].…”
Section: Natural Compoundsmentioning
confidence: 99%